Twins born following assisted reproductive technology: perinatal outcome and admission to hospital. - Hansen, M; Colvin, L; Petterson, B; Kurinczuk, J; de Klerk, N; Bower, C (2009)
BACKGROUND: Compared with spontaneously conceived (SC) singletons, adverse perinatal outcome, neonatal intensive care unit (NICU) admission and hospital admission in infancy are more common in those born following Assisted Reproductive Technology (ART). Similar comparisons for twins have shown conflicting results. METHODS: We investigated perinatal outcome and hospital admission during the first 3 years of life for all twin children born in Western Australia between 1994 and 2000 [700 ART, 4097 SC]. RESULTS: ART twins had a greater risk of adverse perinatal outcome including preterm birth, low birthweight and death compared with SC twins of unlike-sex. In their first year of life, ART twins had a longer birth admission; were 60% more likely to be admitted to a NICU; and had a higher risk of hospital admission. The increased risk of hospital admission continued in the second and third year but was not statistically significant in the third year. CONCLUSIONS: Couples undertaking ART should be aware that in addition to the known increased perinatal risks associated with a twin birth, ART twins are more likely than SC twins to be admitted to a NICU and hospitalized in the first 3 years of life.